Analysis of the significance treatment of henna in the formulation based on fiqh al-hadith - Muhammad Remy Othman,; Khadher Ahmad,; Zulkifli Mohd Yusoff,; Sayidah Asma Basir,; Khalijah Awang, (Penerbit Universiti Kebangsaan Malaysia, 2023)
Henna is a type of plant that is normally used in our society as an accessory to paint their nails, hair and for men, beards. However, it is usually an accessory designed for women. Even so, there are some people in the society who use henna as a treatment for postpartum internal wounds. Through inductive and deductive analysis, the objective of this article is to analyse, from the fiqh al-hadith perspective, on the usage of henna that is explained in the hadiths in order to get a comprehensive explanation of the use of henna that was recommended by the Prophet PBUH so that the discussion can be related with the reality of the proper use of henna in society. The results of the study found that, from the fiqh al hadith perspective, the discussion on the use of henna is [1] Henna as a hair dye to darken grey hair; [2] Henna also acts as an accessory designed for women whether it is for their nails or hair; [3] The law prohibits the use of the colour of henna for men as accessories that resemble women (tasyabbuh); [4] Henna as wound treatments; and [5] Henna for leg pain treatments. Hence, the outcome of this discussion can be developed into a scientific study to prove precisely the use of henna to benefit the society as a whole.